Evapotranspiração e coefciente de cultura da melancia na microrregião de Teresina, PI, Brasil - Ferreira, Valber Mendes [UNESP]; Klar, Antonio Evaldo [UNESP]; Júnior, Aderson Soares Andrade; Bastos, Edson Alves; Oliveira, Simone Raquel Mendes (Lepidus Tecnologia, 2015)
The determination of crop coefficient (Kc) values during the crop development cycle is essential to obtain the water requirements for the culture. The present study aimed to determine the evapotraspiration and Kc on Shadow, Top Gun and Crimson Sweet watermelon cultivars, during different stages of development using the method of soil water balance. The experiment was conducted at Embrapa Meio Norte in Teresina, PI, experimental field, from August to October, 2010. The evapotranspiration reference was estimated by Penman-Monteith, based on meteorological data obtained by an automatic weather station. According to the results, the ETc was 224.4 mm, corresponding to an average of 3.8 mm day-1. The higher water demand was 5.5 mm day-1, obtained at the intermediate phenological stage. The Kc values were 0.39, 0.80, 1.14, 0.59 (Crimson Sweet), 0.35, 0.72, 1.20, 0.30 (Top gun) and 0.34, 0.58, 0.89, 0.55 (Shadow), for initial, growth, intermediate and final phases, respectively.
Watermelon evapotranspiration and crop coefficient in Teresina microregion - Piaui, Brazil
Keywords: Citrullus lanatus; Irrigation management; Kc; Water consumption